Research on Mechanical Characteristics of Asphalt Graded Gravel Layer with Ballast Bed under Train Load - Shu Sun (Shock and Vibration)
This article carries out laboratory tests, driving tests, and discrete element method simulations to study the mechanical properties of ballasted tracks including asphalt graded gravel and the influence of factors such as the thickness of asphalt graded gravel layer and train speed on the dynamic characteristics of the closed structure of asphalt graded gravel. It was discovered that the asphalt graded gravel can improve the bearing capacity of the ballasted track subgrade structure and improve the stability of the ballast bed. Comparative analysis shows that as the depth of the ballast bed increases, the amplitude and frequency of the velocity fitting function of each layer gradually decrease. Appropriately increasing the depth is beneficial to the stability of the ballast bed; the vertical dynamic deformation and dynamic stress decrease with the increase of the thickness of asphalt graded gravel layer; with the increase of train speed, the peak frequency of the corresponding spectrum of asphalt graded gravel layer acceleration increases. There are currently few research studies on the asphalt graded crushed stone structure laid in the ballast bed, especially the mechanical properties of the asphalt graded crushed stone structure laid by the discrete element simulation are still blank. The acceleration of the asphalt graded gravel layer increases corresponding to the peak frequency of the spectrum. The peak frequency of the acceleration response of the asphalt graded gravel layer increases. The research rules can provide a reference for the research and development of shock absorption equipment. The research results of this article can provide technical support for the application of asphalt graded gravel in railway engineering.